Transdermal Delivery of Azilsartan: Formulation Strategies and Performance Evaluation (Asian Journal of Pharmaceutics (AJP), 2024)
Aims: Matrix-type systems were developed in the present study by using various polymers including sodiumcarboxymethyl cellulose and eudragits with various concentrations. Materials and Methods: In the present work,an attempt has been made to develop a matrix-type transdermal therapeutic system comprising of Azilsartanwith different concentrations of sodium carboxyl methyl cellulose and Eudragit using solvent evaporationtechnique. The physicochemical compatibility of the drug and the polymers was studied by infrared spectroscopy.Results and Discussion: The results obtained showed no physical-chemical incompatibility between the drug andthe polymers. The in vitro drug diffusion studies from the formulation were found to be a sustained release effect.All the evaluation parameters obtained from the best formulation were found to be satisfactory. Conclusion: Thedata obtained from the in vitro release studies were fitted to various kinetic models; it was found that drug releasefollows the Peppas model release by diffusion technique from the polymer.